Change of the polarization properties of the human dermis with directions of incident and observation. (July 2023) - Wu, Dongjin; Gao, Wanrong; Chang, Ying
Highlights: To the best of our knowledge, the Mueller matrix of the skin model of the human dermis that varies with the incident angle and the viewing direction is obtained for the first time, and the model can directly obtain the Mueller matrix through numerical simulation. We provide the model Mueller matrix and polarization characteristic parameter curves of the different incident and scattering angles, which gives a basis for the selection of incident and scattering angles when measuring biological samples containing fibrous structures in the future. The possible birefringence of the medium surrounding the dermal collagen fibers is provided by a PS-OCT device. Compare the stabilities of the polarization parameters of the model under different incident angles, and determine that depolarization is the most stable polarization parameter of this model. Abstract: In this work, a simplified cylinder-birefringence optical model of the human skin dermis model is reported. The actual polarization parameters of human fingernail skin were measured. And the accuracy and stability of the Mueller matrix polarization decomposition (MMPD) and the direct Mueller matrix (DMM) methods were compared under different incident and scattering angles. One main novelty of the present work is that the value of birefringence of the skin dermis was obtained from images of living human index finger nails by using a polarization-sensitive optical coherence tomography device. The results obtained in this work provide a basis for the selection of incident and scattering angles when measuring biological samples containing fibrous structures in the future.